Resistance to Pythium root rot and anthracnose among Kenyan common bean genotypes and marker-assisted introgression of resistance genes - Misango, Shamir; Otsyula, Reuben; Arunga, Esther E. (Taylor and Francis, 2022)
ABSTRACT Common bean (Phaseolus vulgaris L.) is an important food legume crop and major protein source in Kenya and many parts of the world. However, the yields are low due to the diseases like anthracnose caused by Colletotrichum lindemunthianum and Pythium root rots. The study, therefore, sought to screen Kenyan common bean genotypes for anthracnose and Pythium resistance and to improve the resistance of local landraces to the two diseases. Local landraces and commercial cultivars were screened for resistance under greenhouse conditions for Pythium and in vitro for anthracnose. The results showed that majority of the landraces were moderately resistant to anthracnose and Pythium root rot. The study further utilized molecular markers linked to anthracnose and Pythium resistance, respectively, to determine their potential to detect specific resistance genes among the test genotypes. None of the markers amplified the test genotypes except the control genotypes pointing toward different resistance genes. Further, cultivars G2333 and KK8 were used as donor parents for anthracnose and Pythium resistance, respectively, in a marker-assisted backcross breeding program involving three high-yielding farmer-preferred landraces. A number of lines were developed that carry both resistance genes. These lines can be advanced for release as new cultivars to enhance common bean production in Kenya.